Development of mathematical models to predict the effect of input parameters on feed rate of a reciprocatory tube funnel feeder - Jain, Anshika; Bansal, Prachi; Khanna, Pradeep (Journal of Production Engineering, 2023)
Rapid industrialisation and technological advancements in assembly processes and the demand for feeding the components in assembly lines has grown significantly. It, therefore, becomes essential to optimize the assembly process. Automated or mechanized assembly can be achieved by the use of feeders. This paper describes the mathematical modelling and performance analysis of a mechanical reciprocatory tube funnel feeder by using design of experiment technique where the adequacy of model was tested by analysis of variance (ANOVA) and significance of regression coefficients is checked by using t-tests. The mathematical model so developed would prove to be useful to establish quantitative relationship between the response parameter and the process parameters like speed, part population and part length.